Tanggung Jawab Sosial dan Lingkungan Perseroan Pada PT Aplikasi Karya Anak Bangsa - Livva, Watnara Hairiyah (Tribuere, 2022)
As technology progresses, more and more companies in the field of technology applications are growing and expanding, one of them is PT. PT Aplikasi Karya Anak Bangsa that moves in the application of technology in the field of transportation. As a corporation under the law of association, PT PT Aplikasi Karya Anak Bangsa must implement the program of social and environmental responsibility of the association as mandated in Act No. 40 of 2007 on Limited Associations. The issue raised is how to regulate social and environmental responsibility of corporations under Act No. 40 of 2007 on limited corporations? And where is the implementation of social and environmental responsibility in the application of the National Children's Work Department? The type of research used is normative juridical research that is descriptive, using secondary data as its primary data, analyzed qualitatively, and drawing conclusions using deductive logic. The results of the research show that the social and environmental responsibility of corporations is regulated in Article 74 of the Law No. 40 of 2007 on Limited Associations and Article 15 letter b of the Act No. 25 of 2007 concerning Capital Plantation and Article 4 of the Regulations of the Governor of the Special District of the Capital of Jakarta No. 112 of 2013 on Corporate Social Responsibility and Environment. The implementation of the social and environmental responsibility of the association carried out by P.T. PT Aplikasi Karya Anak Bangsa is as follows: provision of health supplies for drivers partners, health insurance guarantees for driver partners, assistance in payment of vehicle loans, and others; forms of social responsibility and environment activities conducted among them are the Indonesian Movement Plastic Bag Diet, Voucher Support for Health Energy, and efforts to accelerate the Government's vaccination program.